1998
DOI: 10.1007/bf02475319
|View full text |Cite
|
Sign up to set email alerts
|

Basicities of alumina-supported alkaline earth metal oxides

Abstract: A series of alumina-supported alkaline earth metal oxide catalysts were prepared by recipient-wetness impregnation. These catalysts were characterized by nitrogen-sorption to determine their surface areas and pore size distributions. The basicities of these catalysts were characterized by temperature-programmed des0rption of carbon dioxide. The TPD results demonstrate that all of the catalysts have one-peak profiles. The basicity increases with increasing atomic number of the alkaline earth metal. The alumina-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
0
6
1
Order By: Relevance
“…Our results on the optimal calcination/activation temperature were different comparing to the results of some authors [15][16][17][18][19]22]; the reason may be in a fact that precursors of the CaO-based catalysts were various comparing to the compound used in this experiment. Moreover, in our case, the calcination temperatures below 900 °C were not enough high to cause formation of active crystal phase and activation of surface basic sites, while temperatures over 900 °C may induce undesirable sintering of the catalytic material, hence, changes in surface morphology and particle sizes.…”
Section: Catalyst Structure-activity Relationshipscontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results on the optimal calcination/activation temperature were different comparing to the results of some authors [15][16][17][18][19]22]; the reason may be in a fact that precursors of the CaO-based catalysts were various comparing to the compound used in this experiment. Moreover, in our case, the calcination temperatures below 900 °C were not enough high to cause formation of active crystal phase and activation of surface basic sites, while temperatures over 900 °C may induce undesirable sintering of the catalytic material, hence, changes in surface morphology and particle sizes.…”
Section: Catalyst Structure-activity Relationshipscontrasting
confidence: 99%
“…The increase of the calcination temperature to a certain value caused the increase of the CaO activity; the optimal CaO calcination temperature of 550 °C was recognized. This result was explained by dehydration of Ca(OH) 2 and the transformation of CaCO 3 to CaO [16][17][18], and additionally by the amount of active sites [16][17][18]. The FAME yield of rather more than 90% was achieved by using the CaO catalyst calcined at 550 °C after 120 min of the reaction under the following conditions: catalyst amount, based on the oil weight, %: 1.0; average catalyst particle size, µm: 2.8; reaction temperature: 60 °C; agitation speed, rpm: 900 [17].…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Biodiesel is commonly produced using a soluble catalyst, such as KOH, in the industry but the major drawback of using soluble catalyst is that it may result in soap formation if oil has high free fatty acid and water (Zhang et al, 2003;Meher et al, 2006). Acid, base, or supported enzyme catalysts were used as heterogeneous catalysts in the transesterification of vegetable oils (Van Gerpen, 2005;Xie and Li, 2006;Chen et al, 1998). For example, Suppes et al (2003) reported metal ion-exchanged zeolites were highly active in the transesterification of soybean oil at 100-150°C temperature range in 4-24 h. Enzymatic catalysts, such as lipases, are environmentally friendly but they are expensive and also decrease of activity was observed when immobilized on a support material (Severac et al, 2011).…”
Section: Introductionmentioning
confidence: 99%